2020
DOI: 10.3390/ma13071536
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of CdTe Thin Films for Solar Energy Water Splitting

Abstract: CdTe thin films have been prepared by electrochemical deposition. The morphological, structural, and optical properties of CdTe thin films deposited with different deposition time were investigated, and the influence of film thickness on the photoelectric characteristics of CdTe thin films was studied. At the deposition time of 1.5 h, CdTe thin films had good optical properties and the photocurrent reached 20 μAcm−2. Furthermore, the Pt/CdS/CdTe/FTO structure was prepared to improve its PEC stability and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…To enhance the photocurrent of the CdTe photocathode, most reported works fabricated the CdTe/CdS heterojunction and used the noble metal Pt as the HER co-catalyst to improve H 2 evolution efficiency. , , In this work, we employed the earth-abundant and low-cost metal Ni as the HER co-catalyst to boost the overall PEC performance of the CdTe-based photocathode. To optimize the thickness of the Ni layer, we deposited 2, 5, 10, and 50 nm Ni layers on the CdTe/CdS/TiO 2 photocathodes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To enhance the photocurrent of the CdTe photocathode, most reported works fabricated the CdTe/CdS heterojunction and used the noble metal Pt as the HER co-catalyst to improve H 2 evolution efficiency. , , In this work, we employed the earth-abundant and low-cost metal Ni as the HER co-catalyst to boost the overall PEC performance of the CdTe-based photocathode. To optimize the thickness of the Ni layer, we deposited 2, 5, 10, and 50 nm Ni layers on the CdTe/CdS/TiO 2 photocathodes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cadmium telluride (CdTe) is an attractive candidate for hydrogen production via PEC water splitting due to its excellent optical absorption characteristics and band structure. As a direct semiconductor with a band gap of 1.5 eV, CdTe exhibits a wide range absorption from ultraviolet to infrared sunlight (until 830 nm) and a high absorption coefficient of >10 4 cm –1 at the wavelengths smaller than 800 nm. , It has been extensively demonstrated that CdTe is an excellent absorbing material in the application of photovoltaic devices. Since the pioneering work of Ohashi et al in 1977, , p -type CdTe as a photocathode for the PEC water splitting has also attracted much interest. Recently, it has been demonstrated that the CdTe-based multilayer photocathodes with the deposited noble metal platinum (Pt) as the hydrogen evolution reaction (HER) co-catalyst exhibit an increased photocurrent and a significant shift of the onset potential. , It is reported that the Au/Cu/CdTe (CdCl 2 )/CdS/Pt photocathode has shown a remarkably high incident photon-to-current conversion efficiency (IPCE) of >95% at 560–660 nm with an applied potential of 0 V versus reversible hydrogen electrode (V RHE ) . However, most reported CdTe-based photocathodes employed noble-metal Pt as the HER catalyst, ,, which increases the cost of the PEC cells and hinders the future practical applications for low-cost hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CdS/CdTe solar cell has been recognized as one of the potential possibilities for developing sound photovoltaic systems [5]. CdTe has recently gained attention due to its many applications, such as photovoltaics [6], x-ray sensors [7], solar energy water splitting [8], imaging detectors [9], optoelectronics [10], and radiation detectors [11].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Cadmium-chalcogenides-based materials and composites are among the most studied materials due to their broad applicability in photocatalysis. [23][24][25][26][27][28] For instance, CdS nanocrystals (NCs) are known to show photostability under light irradiation at 350 nm (excitation intensity of about 2 mW cm À 2 ). [29] Similarly, the photostability in CdSe quantum dots (QDs) is enhanced by the organic ligands (such as aromatic dithiocarbamates) by allowing the ligands to delocalize the exciton state more effectively.…”
Section: Introductionmentioning
confidence: 99%